2017
DOI: 10.1038/s41598-017-07406-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in disordered mesoporous solids

Abstract: Fluids confined in mesoporous solids exhibit a wide range of physical behavior including rich phase equilibria. While a notable progress in their understanding has been achieved for fluids in materials with geometrically ordered pore systems, mesoporous solids with complex pore geometries still remain a topic of active research. In this work we study phase transitions occurring in statistically disordered linear chains of pores with different pore sizes. By considering, quite generally, two phase change mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…Microscopic details of how these effects emerge in long chains were explored using combinations of only few pore sections using GCMS simulations (Nguyen et al, 2013a). Analogous studies, but with notably longer chains, have proven the emergence of cooperativity effects and validated the conclusions made earlier (Kondrashova and Valiullin, 2013, 2015; Schneider et al, 2017).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Microscopic details of how these effects emerge in long chains were explored using combinations of only few pore sections using GCMS simulations (Nguyen et al, 2013a). Analogous studies, but with notably longer chains, have proven the emergence of cooperativity effects and validated the conclusions made earlier (Kondrashova and Valiullin, 2013, 2015; Schneider et al, 2017).…”
Section: Introductionsupporting
confidence: 80%
“…Similarly, for the desorption transition one has to consider two products of (i) the equilibrium kernel θ g ( x, p ) with the PSD of the empty sections and of (ii) the metastable kernel θn(x,p) with the PSD of the filled sections. An approximate solution for Equations (2) and (3) is presented in the work by Schneider et al (2017) and the exact derivation can be found elsewhere (Schneider and Valiullin, submitted). In what follows, we present the final results.…”
Section: Serially Connected Pore Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of irregularities in the SBA-15 mesoporous channels was also suggested from diffusion studies by means of pulse field gradient nuclear magnetic resonance [33]. In this view, the sub-domains inside the same pore can no longer be considered independent of each other and the predicted isotherms resemble the isotherms usually obtained on solids characterized by disordered pore networks [34]. To account for the interactions among the sub-domains, the phenomena of advanced adsorption/condensation and pore blocking have been introduced respectively for the adsorption and desorption mechanisms.…”
Section: Introductionmentioning
confidence: 83%
“…The first formulation of the model considers a solid made of regular independent cylindrical pores. The second formulation of the model considers nonregular independent cylindrical pores for an improved correlation of the scanning curves, which is similar to the serially connected pore model [34].…”
Section: Introductionmentioning
confidence: 99%